René Descartes: Meditations on First Philosophy : With Selections from the Objections and Replies - Cottingham, John (Cambridge : Cambridge University Press, 2013)
Descartes's Meditations on First Philosophy, published in Latin in 1641, is one of the most widely studied philosophical texts of all time, and inaugurates many of the key themes that have remained central to philosophy ever since. In his original Latin text Descartes expresses himself with great lucidity and elegance, and there is enormous interest, even for those who are not fluent in Latin, in seeing how the famous concepts and arguments of his great masterpiece unfold in the original language. John Cottingham's acclaimed English translation of the work is presented here in a facing-page edition alongside the original Latin text. Students of classical philosophy have long had the benefit of dual-language editions, and the availability of such a resource for the canonical works of the early-modern period is long overdue. This volume now makes available, in an invaluable dual-language format, one of the most seminal texts of Western philosophy.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: First philosophy; Methodology; Knowledge, Theory of